2014
DOI: 10.1016/j.drugpo.2013.07.003
|View full text |Cite
|
Sign up to set email alerts
|

“I felt like a superhero”: The experience of responding to drug overdose among individuals trained in overdose prevention

Abstract: Background Overdose prevention programs (OPPs) train people who inject drugs and other community members to prevent, recognise and respond to opioid overdose. However, little is known about the experience of taking up the role of an “overdose responder” for the participants. Methods We present findings from qualitative interviews with 30 participants from two OPPs in Los Angeles, CA, USA from 2010–2011 who had responded to at least one overdose since being trained in overdose prevention and response. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
85
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 45 publications
10
85
1
Order By: Relevance
“…Many SIEs stated that this intervention made them feel “empowered” as similarly reported in previous studies (Marshall et al, 2017; Wagner et al, 2014). Participants also stated that being supplied with naloxone made them feel “equipped” so that they could act in the event of an overdose:

“ Feeling confident and equipped to be an agent in saving someone’s life and that to a person is just invaluable…to be at work and – or somewhere else and know that you can do something .”

[Sevn, male]

“ I learned a lot.

…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Many SIEs stated that this intervention made them feel “empowered” as similarly reported in previous studies (Marshall et al, 2017; Wagner et al, 2014). Participants also stated that being supplied with naloxone made them feel “equipped” so that they could act in the event of an overdose:

“ Feeling confident and equipped to be an agent in saving someone’s life and that to a person is just invaluable…to be at work and – or somewhere else and know that you can do something .”

[Sevn, male]

“ I learned a lot.

…”
Section: Resultssupporting
confidence: 73%
“…Two authors (BWS and LE) with qualitative expertise separately coded one transcript, using a preliminary list of a priori codes based on topical domains addressed in the interview protocol (e.g., willingness to intervene, empowerment, etc.) adapted from similar studies (Marshall et al, 2017; Wagner et al, 2014). The coders met regularly during this process to discuss emergent themes and the addition of new code categories (e.g., importance of staying calm, requesting emergency medical services (EMS) and not police, etc.).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, participants demonstrated how they had acquired new skills and knowledge from their training, were willing to prioritize this new formal knowledge above non-evidence-based strategies they had used in the past (contrary to [21]) and felt empowered by their ability to respond [36,44,61,62]. This includes their ability to rapidly assess a scene for signs and symptoms of overdose, anticipate and empathize with a victim's withdrawal symptoms, withhold or titrate a naloxone dose depending on the drugs probably taken, communicate effectively with a confused victim and persuade a reluctant patient to accept professional medical care.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple ecological and other observational studies of community naloxone distribution programs demonstrated that PWID can learn overdose prevention and administer naloxone successfully (Doe-Simkins, Walley, Epstein, & Moyer, 2009; Green, Heimer, & Grau, 2008; Seal et al, 2003; Seal et al, 2005; Tobin, Sherman, Beilenson, Welsh, & Latkin, 2009), and suggested potential ancillary benefits such as decreased substance use, social connection, and empowerment (Wagner et al, 2014; Wagner et al, 2010). San Francisco documented a dramatic reduction in heroin overdose mortality in the early 2000s, from approximately 180 heroin overdose deaths per year in the late 1990s to 10-11 per year from 2010-2012, although some of that decrease was a result of transitions to prescription opioids (Visconti, Santos, Lemos, Burke, & Coffin, 2015).…”
Section: Introductionmentioning
confidence: 99%